1979
DOI: 10.1046/j.1537-2995.1979.19279160286.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype i Associated with Congenital Cataract in Japanese

Abstract: A Japanese family with two siblings of phenotype i is presented. Both had a past history of surgical treatment for congenital cataract. In Japan, 18 individuals of phenotype i, including our case, have been found in ten unrelated families. Seventeen of them had congenital cataract. Cataract was not found in any of the 45 phenotype I members in these families. It is briefly discussed why these two linked and quite rare genes were found in combination only in Japanese persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…In Asian populations, i blood group phenotype of erythrocytes is clearly associated with the onset of cataracts, while the relationship is less clear in Caucasian populations (18,19,22,28,37). IGnT C (IGnT3) is responsible for I antigen expression on erythrocytes (11,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asian populations, i blood group phenotype of erythrocytes is clearly associated with the onset of cataracts, while the relationship is less clear in Caucasian populations (18,19,22,28,37). IGnT C (IGnT3) is responsible for I antigen expression on erythrocytes (11,41).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis of i blood group expression on erythrocytes has been clarified recently (11,41); null mutations in IGnT C (IGnT3) are responsible for the phenotype. In Asians, the blood group i phenotype is associated with congenital cataracts (18,28,37), whereas the association is less pronounced in Caucasian populations (19,22). Analysis of the IGnT gene has suggested that congenital cataracts are caused by null mutations of common exons (41).…”
mentioning
confidence: 99%
“…15,16 In addition, it was reported that the adult i phenotype in Japanese persons is often associated with congenital cataracts. 33 The i blood type of individuals in the present study is associated with cataracts, as described in "Materials and methods." However, it has been reported that the i blood type of white persons has a reduced association with congenital cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…The association can be explained by either a close linkage between independent I-and cataract-related genes or a pleiotropic effect of the gene responsible for the adult i phenotype on the development of cataracts. 24,25 Because of the reduced association between adult i phenotype and congenital cataracts in the white population, the former hypothesis of a close linkage of 2 independent genes was suggested to be the tenable one. 28 It has been proposed that the adult i phenotype in Asians, and in some whites, may result from the deletion of a small chromosomal region that also encompasses a nearby gene, and this results in the development of cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite its rareness, the adult i phenotype has attracted considerable attention because of its association with congenital cataracts. Yamaguchi et al [24][25][26] first reported the observation of an association between the adult i phenotype and congenital cataracts among Japanese. Linkage of adult i phenotype and congenital cataracts has been observed in 3 Taiwanese pedigrees.…”
Section: Introductionmentioning
confidence: 99%